Pengaruh Inklusi Keuangan Terhadap Kesejahteraan Rumah Tangga: Pendekatan Diversifikasi Konsumsi Berbasis Entropi - Setiawati, Indah Sopia; Joan Marta (Universitas Negeri Padang, 2025)
This study aims to analyze the impact of financial inclusion on household welfare in Indonesia using a consumption diversification approach based on entropy. The data used is sourced from the 2020 National Socioeconomic Survey (SUSENAS) and analyzed using the Two-Stage Least Squares (2SLS) method. The Theil entropy index is applied to measure the level of household consumption diversification as an indicator of welfare. The results show that financial inclusion, through ownership of savings accounts and insurance, positively affects household consumption expenditure, while access to formal credit has a negative impact. Education level of the household head and region of residence also significantly influence consumption, with households in Java tending to have higher expenditure. Household consumption has a negative relationship with food consumption diversification but a positive relationship with non-food diversification, reflecting a shift in consumption patterns consistent with Engel’s Law. Furthermore, consumption diversification patterns are influenced by region, where households outside Java exhibit more diverse food consumption, while those in Java show greater non-food consumption diversity. Overall, access to financial services can encourage diversified consumption patterns that serve as key indicators in assessing household welfare.